KEKUATAN ORGANISASIONAL DAN SISTEM DALAM PENCEGAHAN FRAUD: SUATU TINJAUAN SYSTEM LITERATURE REVIEW - Rahmarta, Vandy; Pontoh , Grace T.; Said, Darwis (SUBSTANSI, 2024)
Research objective: This article discusses the importance of fraud prevention in organizations, focusing on both public and non-public sectors. A deep literature review explores factors influencing the successful implementation of fraud prevention systems, such as the fraud triangle theory, attribution theory, stewardship theory, and organizational culture. Method: The research employs a Systematic Literature Review (SLR) method to identify, evaluate, and synthesize findings from 32 journals related to fraud prevention. The study highlights the need for increased investment in developing and promoting effective whistleblowing systems, e-Procurement implementation, and fostering an organizational culture that supports ethical values as strategies for fraud prevention in both public and non-public sectors. Research findings: It provides policy recommendations and conclusions based on the findings of various related studies, emphasizing the effectiveness of fraud prevention measures. Practical implication: The research also lays a strong foundation for the development of more effective and comprehensive fraud prevention policies and practices, ultimately enhancing integrity and transparency across various organizational and governmental levels.